Survival in HIV-infected Asymptomatic Cryptococcal Antigenemia without CSF Positivity Treated with Fluconazole Did Not Differ from Cryptococcal Antigen (CrAg) Negative with CD4 <150. (4th October 2017) - Beyene Tufa, Tafese; Girma, Anteneh; Rajasingham, Radha; Boulware, David
Abstract: Background: Cryptococcal meningitis causes 15% of HIV/AIDS-related deaths; however, meningitis can be prevented by early screening and giving preemptive treatment to a high-risk population. Methods: We screened HIV-infected patients whose CD4+ count ≤150/µL for cryptococcal antigen (CrAg) from the left over plasma after CD4 count testing at Adama and Asella hospitals in Ethiopia. We conducted a prospective case–control study comparing the 6-month survival outcomes of 51 plasma CrAg+ patients with 100 randomly selected CrAg-negative patients from CrAg screening registration book within the same CD4 count ranges. CrAg+ patients were treated with appropriate antifungal drugs and both groups initiated HIV therapy according to national treatment guideline. All CrAg+ patients were offered lumbar puncture (LP) to exclude cerebrospinal fluid (CSF) CrAg-positivity. CrAg+ patients without central nerve system (CNS) disease were treated with fluconazole 800 mg/day until starting HIV therapy and 400 mg/day thereafter for 8 weeks. CSF CrAg+ patients were treated with fluconazole 1, 200 mg/day. Results: CrAg was detected in 6.2% ( n = 51)of remaining plasma among 817 HIV-infected persons with CD4 ≤ 150/µL screened from August 2014 to March 2016. The mean CD4 count was 47 cells/µL among CrAg+ and 73 cells/µL in randomly selected CrAg-negative participants respectively. After 6-months, 49% (25/51) of CrAg+ and 19% of (19/100) CrAg-negative patients were dead or lost to follow-up ( P < 0.001). Among asymptomatic cryptococcal antigenemia (plasma CrAg+ but CSF CrAg-negative), the 24% (4/17) mortality rate did not differ from 19% mortality in plasma CrAg-negative (odds ratio 1.31, 95% CI: 0.38–4.5; P =  0.66). Conclusion: Mortality rate is higher among plasma CrAg+ than CrAg-negative HIV-infected with CD4 counts <150 cells/µL. However, survival did not differ between asymptomatic cryptococcal antigenemia (CSF CrAg negative) persons treated with oral fluconazole and CrAg-negative HIV-infected persons. Disclosures: All authors: No reported disclosures.